Praemium Erasmianum : SMA Cahiers 15. - Fuchs, Rudi H.; Heaney, Seamus (Amsterdam : Stedelijk Museum Amsterdam, 1998)
Beuys, Joseph ; Cézanne, Paul ; Dibbets, Jan ; Heaney, Seamus ; Herold, Georg ; Judd, Donald ; Klein, Yves ; Kounellis, Jannis ; Lüpertz, Markus ; Malevich, Kasimir ; Nauman, Bruce ; Picasso, Pablo ; Schouten, Marien ; Schwitters, Kurt
biografie
Praemium Erasmianum, Stedelijk Museum Amsterdam, 14.11.1998 - 10.1.1999
Nederlands & Engels
boek